The associations of gut microbiota, endocrine system and bone metabolism - Tu, Ye; Kuang, Xinyi; Zhang, Ling; Xu, Xin (Frontiers in Microbiology, 2023)
Gut microbiota is of great importance in human health, and its roles in the maintenance of skeletal homeostasis have long been recognized as the “gut-bone axis”. Recent evidence has indicated intercorrelations between gut microbiota, endocrine system and bone metabolism. This review article discussed the complex interactions between gut microbiota and bone metabolism-related hormones, including sex steroids, insulin-like growth factors, 5-hydroxytryptamine, parathyroid hormone, glucagon-like peptides, peptide YY, etc. Although the underlying mechanisms still need further investigation, the regulatory effect of gut microbiota on bone health via interplaying with endocrine system may provide a new paradigm for the better management of musculoskeletal disorders.